Oviductal transcriptional profiling of a bovine fertility model by next-generation sequencing - Gonella-Diaza, Angela Maria (Genom Data, 2017)
In cattle, the oviduct plays a fundamental role in the reproductive process. Oviductal functions are controlled by the ovarian sex steroids: estradiol and progesterone. Here, we tested the hypothesis that the exposure to contrasting sex steroid milieus differentially impacts the oviductal transcriptional profile. We manipulated growth of the pre-ovulatory follicle to obtain cows that ovulated a larger (LF group) or a smaller (SF group) follicle. The LF group presented greater proestrus/estrus concentrations of estradiol and metaestrus concentrations of progesterone (Gonella-Diaza et al. 2015 [1], Mesquita et al. 2014 [2]). Also, the LF group was associated with greater fertility in timed-artificial insemination programs (Pugliesi et al. 2016 [3]). Cows were slaughtered on day 4 of the estrous cycle and total RNA was extracted from ampulla and isthmus fragments and analyzed by RNAseq. The resulting reads were mapped to the bovine genome (Bos taurus UMD 3.1, NCBI). The differential expression analyses revealed that 325 and 367 genes in ampulla and 274 and 316 genes in the isthmus were up-regulated and down-regulated in LF samples, respectively. To validate the RNAseq results, transcript abundance of 23 genes was assessed by qPCR and expression patterns were consistent between the two techniques. A functional enrichment analysis was performed using Database for Annotation, Visualization and Integrated Discovery (DAVID) software. Processes enriched in the LF group included tissue morphology changes (extracellular matrix remodeling), cellular changes (proliferation), and secretion changes (growth factors, ions and metal transporters). An overview of the gene expression data was deposited in the NCBI's Gene Expression Omnibus (GEO) and is accessible through the accession number GSE65681. In conclusion, differences in the peri-ovulatory sex steroid milieu modify the oviductal gene expression profiles. Such differences may be associated with the greater fertility of the LF cows. This dataset is useful for further investigations of the oviductal biology and the impact of sex-steroid on the female reproductive tract.